Biodegradable polymer networks via triazolinedione-crosslinking of oleyl-functionalized poly(ε-caprolactone). (April 2017) - Basko, Malgorzata; Bednarek, Melania; Vlaminck, Laetitia; Kubisa, Przemyslaw; Du Prez, Filip E.
Graphical abstract: Highlights: Functional PCLs with α, ω-oleyl end groups were synthesized by coordination ROP. Polyester networks were prepared by coupling of PCL polymers via bifunctional TAD crosslinkers. Optimal conditions for networks synthesis were found by changing crosslinking parameters. Thermal and mechanical properties of networks were determined. Abstract: The formation of biodegradable polymer networks by the crosslinking of tailor-made poly(ε-caprolactone) (PCL) via the ultrafast 1, 2, 4-triazoline-3, 5-dione (TAD) chemistry has been demonstrated. First, a series of α, ω-oleyl terminated PCL was prepared by a two-step, one-pot synthesis that was initiated by the coordination ring opening polymerization of ε-caprolactone, resulting in prepolymers bearing both an oleyl and hydroxyl end group, which were subsequently coupled by means of a diisocyanate. Network formation was performed via Alder-ene reaction of two different bifunctional triazolinediones (bisTADs) with the oleyl end groups. Different crosslinking parameters were studied in order to find the optimal conditions for the preparation of sufficiently strong polymer networks. Besides the determination of thermal and mechanical properties, as well as the susceptibility to hydrolytic degradation, of the obtained PCL-network, also the influence of the PCL molecular weight, nature of the TAD crosslinker and crosslinking stoichiometry were determined.